A low-complexity linear precoding and power allocation scheme for downlink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2013 Asilomar Conference on Signals, Systems and Computers, 2014)
In this paper, we present a low-complexity linear precoding and power allocation scheme for downlink massive multiple-input multiple-output (MIMO) systems. The optimization criteria adopted for the proposed precoding and power allocation scheme are maximization of the sum rate and maximization of the minimum user rate, respectively. The presented precoder is based on a matrix polynomial and can closely approach the sum rate and the minimum user rate of the optimal regularized zero forcing (RZF) precoder, which requires a matrix inversion, and performs substantially better than the simple conjugate beamforming (BF) precoder. Our simulation results show that the proposed precoding scheme with a low order matrix polynomial can approach the sum rate and the minimum user rate of the optimal RZF precoder. We also present analytical results for the asymptotic sum rate and the asymptotic minimum user rat